4CPS-320 Improving medication adherence and patients' experience after heart transplant using a multilevel eHealth intervention: the mHeart clinical trial. (14th March 2021) - Gomis Pastor, M; Mirabet Perez, S; De Dios López, A; Roig Mingell, E; Brossa Loidi, V; Lopez Lopez, L; Ros Abarca, S; Mas Malagarriga, N; Jorba Bertran, N; Medina Catalan, D; Mangues Bafalluy, MA
Abstract : Background and importance: Multimorbidity and therapeutic complexity are undermining health outcomes in chronic populations. Medication non-adherence may be a consequence of this complexity and is a direct cause of graft loss and death after a heart transplant (HTx). Effective interventions to improve medication adherence and lifestyle habits require a proactive interdisciplinary team and integrated care models. The development and implementation of internet based health technologies (eHealth) may lead to implementation of such chronic care programmes in clinical practice. Aim and objectives: To improve recipients' adherence to immunosuppressive medication (IS). Secondary objectives were to improve patients' experience of their therapeutic regimens (TR) and to optimise clinical practice. Material and methods: An eHealth model was implemented in a HTx hospital's outpatient clinic. The software developed (mHeart) was a mobile and website application (https://n9.cl/ajut ). The model was validated previously in a pilot study. 1 For this purpose, an intensive, individually tailored, behavioural based multicomponent intervention performed using the mHeart features in an interdisciplinary environment was established. The study design is described in figure 1 . Results: A total of 134 chronic stage HTx patients (mean age 55 (SD 14) years) were included (intervention n=71; control n=63). The mean follow-up was 1.6 (SD 0.6) years. At the end of the study, 86% were engaged with mHeart. Patients' experience of TR significantly improved in the intervention group (IG) versus the control group (CG): degree of inconvenience perceived by the patient (p=0.002), patient's knowledge of their regimen intakes (p=0.019), drugs names (p=0.006), drugs doses (p=0.030) and drugs indications remembered (p=0.003). In addition, patient's awareness of the consequences of non-adherence significantly improved (p<0.01) and the number of adverse effects reported was significantly reduced to 3±2 in all groups (p=0.000). The non-adherence rate significantly improved in the IG versus the CG according to the SMAQ questionnaire (85% vs 46%) (OR=6.7 (2.9; 15.8); p=0.000). Because of the online follow-up, patients' in-clinic appointment needs with the clinical pharmacist and the intensity of the follow-up were significantly reduced in the IG (65%) versus the CG (35%) (OR=3.4 (1.7; 6.9); p=0.001). Conclusion and relevance: mHeart has been demonstrated to improve recipients' adherence to IS (85% IG vs 46% CG), patients' experience of therapeutic regimens and to reduce in-clinic facilities because of the mHeart follow-up. Innovative research projects on health institutions are typically short lived practices with lack of scalability to usual care. This was a priority for the mHeart study, and the intervention was extended into clinical practice in January 2019. References and/or acknowledgements: Gomis M, et al . JMIR mHealth and uHealth 2020. Conflict of interest: No conflict of interest